EDUCATION IN FEMINIST DISCOURSE: A GENRE ANALYSIS OF REMARKS BY PRESIDENT FAUST IN THE W50 SUMMIT, HARVARD BUSINESS SCHOOL, BOSTON, MASS APRIL 4, 2013 - Al Qaisiya, Fatima Mousa Mohammad; Bani-Khaled, Turki Ahmad Ali (European Scientific Journal, ESJ, 2015)
This paper examines the theme of education in feminist discourse with particular reference to a speech given by a prominent academic leader (Drew Faust, President and Professor of Harvard University). This is done by reviewing related literature on feminist discourse and public speaking of political and academic leaders. Using insights from genre analysis theory and discourse analysis models, this study investigates the speech in relation to theme, notions, communicative functions, and rhetorical features. The results showed that content and style were influenced by purpose and contextual factors of the occasion. The academic background of the speaker (history) is reflected throughout the speech. Therefore, the rhetorical strategies employed included quoting and narrating in the form of anecdotes. Arguing and giving evidence from documented resources was noted to be the major strategy. The overall framework of the speech seems to be a problemsolution model where questions are raised and answers are provided in relation to the theme of women’s education.